Univariate Analysis of Stunting Determinant Characteristics in Toddlers - Kusiyono, Kusiyono; Susianto, Susianto; Wahyuniar, Lely (Jurnal Medisci, 2025)
Background. Stunting is a chronic nutritional problem that is still a public health challenge, especially in toddlers, because it has a long-term impact on physical growth, cognitive development, and productivity in the future. Purpose. This study aims to determine the characteristics of stunting determinants in toddlers aged 6–59 months in Pekalipan Village, Cirebon City in 2025. Method. The study used an analytical observational design with a cross sectional approach. The population in this study was all toddlers aged 6–59 months in the study area, with a sample of 153 respondents. Data analysis was carried out univariate to illustrate the distribution of characteristics of the research variables which included maternal education, maternal age at birth, birth weight, exclusive breastfeeding status, immunization completeness, history of infectious diseases, and feeding patterns.Results. The results showed that most mothers had a high level of education (80.4%) and were at a non-risk age at childbirth (83.0%). The majority of toddlers were born with normal weight (92.8%), received exclusive breastfeeding (74.5%), and had complete immunization status (87.6%). Most of the toddlers had no history of infectious diseases (92.2%), but most respondents had improper feeding patterns (86.9%). The prevalence of stunting in toddlers aged 6-59 months in Pekalipan Village is 19.0%.Conclusion. The conclusions of this study show that although most of the determinant characteristics are in the good category, improper feeding patterns are still the dominant problem that has the potential to contribute to the incidence of stunting. Therefore, it is necessary to strengthen nutrition education and proper parenting as an effort to prevent stunting in toddlers